Analysis of the Implementation of Stunting Handling Policy Programs - Devi Kurniati; Rukmaini Rukmaini; Retno Widowati (GLOBAL HEALTH SCIENCE GROUP, 2026)
The prevalence of stunting in Bogor City in 2024 will be 18.2%. The national target is 14%. Policy analysis is needed to identify the success and obstacles of stunting management policy programs in the community. To conduct an analysis of the implementation and effectiveness of stunting handling policy programs in Bogor City based on stakeholder information. Qualitative descriptive research with in-depth interviews and observations of 16 informants consisting of (Head of Health Office, Head of Health Center, Coordinating Midwife, Posyandu Cadres, and Toddler Women) in Tanah Sareal and South Bogor Districts, Bogor City. Evaluation criteria based on William N. Dunn. Data were analyzed using NVivo 15 through thematic analysis. Data analysis produced 5 major themes, namely (program management and leadership, labor and cost barriers, social problems and citizens' habits, changes in officers' habits and responses, suggestions and expectations for the future), 12 categories and 65 codes. The policy runs effectively through the commitment of regional leaders (cross-sector coordination) and digital innovation of virtual referrals (Important Mess). The efficiency aspect is hampered by double input, limited nutritional personnel, and time-lag problems of logistics data. Socioculturally, parental denial and traditional parenting are challenges. However, the responsiveness of officers through the action of